Task-based access control mode of peer-to-peer network based on fuzzy theory - Hao LIU; Lian-ming ZHANG; Zhi-gang CHEN (Tongxin xuebao)
The opening and self-organization features of P2P network brings a series of security risks,andthe traditional access control model is not suitable for P2P network as it is a kind of distributed management system.Task-based access control mode of P2P network was proposed based on fuzzy theory.And the formalization description and analysis of the model was also proposed.The risk value of each transaction was calculated through hierarchy process analysis and fuzzy comprehensive evaluation.In this model,according to the risk value of each transaction,the dynamic management of ac-cess authority was realized by extending task-basedaccess control model.The results show that this model can restrain the success of noncooperative nodes transaction and raise the success of the whole P2P network system transaction,thus improving the security of P2P network system.